Management of Hepatitis-B Virus Infection in Immunocompromised Children: A Single Center Experience. Issue 4 (April 2021) - Calvo, Pier Luigi; Pinon, Michele; Dell'Olio, Dominic; Carpino, Andrea; Biasin, Eleonora; Pizzol, Antonio; Catalano, Silvia; Peruzzi, Licia; Rigazio, Caterina; Cisarò, Fabio; Opramolla, Anna; Asaftei, Sebastian Dorin; et al.
ABSTRACT: Objectives: The aims of the study was to expand the pediatric experience on hepatitis-B virus (HBV) reactivation, a known complication in patients with hematologic malignancies or on immunosuppression. Methods: Retrospective appraisal of HBV therapy/prophylaxis in immunocompromised children, studied from April 2006 to March 2020. Results: Eighteen HBV-positive patients, 5 girls, median age 11.1 (4.1--17.9) years were included. Seventeen of 18 were immunosuppressed at HBV-infection diagnosis. Seventeen were at high risk of reactivation, 1 at moderate risk. Five of 18 had acute hepatitis B as first infection or reactivation, 6 had HBeAg-positive infection, 1 an HBeAg-negative infection and 6 HBsAg-negative infection. Median follow-up was 2.7 (0.7--12.5) years. No HBV-related mortality was observed. Prophylaxis had to be repeated in 1. Lamivudine was used in 6/12 viremic patients and HBV-DNA negativization obtained in 2/6 (33%). Tenofovir-DF was used in 2/12 and entecavir in 4/12: 100% attained HBV-DNA negativization. Therapy had to be switched from tenofovir-DF to entecavir in 1 patient because of renal impairment. Virological breakthroughs were observed in 1 lamivudine-treated patient, leading to a hepatitis flare; 1 patient on entecavir had a hepatitis flare at immunoreconstitution. Mortality was 33% in the HBsAg-positive group. Seven prophylactic treatments were administered to 6 patients with HBsAg-negative infection: tenofovir-DF in 2 HBV-DNA-positive, lamivudine in 5 HBV-DNA-negative, without reverse HBsAg seroconversion, morbidity or mortality. Conclusions: There is a residual risk of acute hepatitis B in immunocompromised children, mortality rate was substantial, potentially related to the delays in commencing chemotherapy caused by liver dysfunction. Tenofovir-DF or entecavir are the drugs of choice for HBV treatment in immunocompromised children. Abstract : Supplemental Digital Content is available in the text